Treatment of post-phlebitic disorders by venous saphenous - femoral contro - lateral anastomosis - Palma, Eduardo; Risi, Francisco; del Campo, Francisco; Tobler, Héctor (Cirugía del Uruguay, 2020)
Presented at session 25th June 1958